A New Genus and Species of Isotomidae (Collembola) - Peter F. Bellinger (Psyche: A Journal of Entomology)
In the course of an investigation of the soil fauna of some localities in Connecticut2, a number of species of Collembola were found which do not appear to have been described. One of these is the subject of the present paper. Others will be dealt with in future contributions, as sufficient material becomes available.